78.4k views
4 votes
?????????????? Help me

?????????????? Help me-example-1
User Seanhodges
by
5.7k points

1 Answer

1 vote

Answer:

Explanation:

When we use the distributive property for expanding polynomial products, we often use it in the form ...

(a +b)c = ac +bc

Here, we have ...

(a +b) = (x -1) ⇒ a=x, b=-1

c = (4x+2)

So, the proper application of the distributive property looks like ...

(a +b)c = ac +bc

(x -1)(4x +2) = x(4x+2) -1(4x+2) . . . . . different from the work shown

We must conclude ...

The distributive property was not applied correctly in the first step.

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.